The Geographical Location as a Limitation for Starting Entrepreneurial Initiatives and Career Development - Deneva, Aneta; Hristova, Veneta; Pavlov, Daniel; Blazheva, Violeta; Kostov, Ivaylo; Angelova, Denislava; Petrova, Mariana (European Journal of Sustainable Development, 2022)
From the perspective of entrepreneurship, the geographical location is one of the important barriers/prerequisites for business development. Its role and place in the development of family entrepreneurship and the career development of young people has been relatively poorly studied. The aim of this paper is to provide an emperical research on the influence of the geographical location for starting entrepreneurial initiatives and career development. The object of this research are students having major or minor classes in the field of entrepreneurship from Albania, Bulgaria, Poland, Romania, Russia and Serbia. The subject of this research is on their attitude for career development in the field of family entrepreneurship and their geographical location. A standartised printed questionnaire has been used with Lickert scale for collecting the answers, translated into the national language of the respondents. The results are given in tables to compare the student intentions and outline their similarities. This paper could help the involved twelve universities to improve their teaching methods in a way their students to perceive the advantages of the geographical location and become part of the the regional entrepreneurs and companies.